ANALISIS NILAI PERUSAHAAN PADA PERUSAHAAN SUBSEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wardah Hamidah (2021)
This research is quantitative research to find out if the capital structure, size of the company and profitability have an influence on the value of the company on the Indonesia Stock Exchange. This study used purposive sampling, and as many as 39 companies that meet the sample kriteria. Hypothesis testing using data panel regression with Eviews 9 and a significant level of 5%. The hypothetical test result is that (1) the capital structure negatively affects the company's value (2) the size of the company positively affects the company's value (3) profitability does not affect the value of the company